Development of an MPS Distribution Station Jobsheet Based on Outseal PLC for Electropneumatic Control Learning - Nurafni Fajarna Do Ahmad; Oriza Candra (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study aimed to develop a jobsheet based on the Modular Production System (MPS) Distribution Station using an Outseal PLC for electropneumatic control learning in vocational schools. The study was motivated by the suboptimal use of MPS facilities and the absence of structured practical learning guidelines, which led to students’ difficulties in understanding the relationship between theoretical concepts and industrial applications. This research employed a Research and Development (R&D) method using the ADDIE model, limited to the development stage. The developed jobsheet was validated by three experts consisting of material and media validators. Data analysis was conducted using Aiken’s V to determine the validity level of the product. The results showed that the material aspect obtained a validity value of 0.78, while the media aspect obtained 0.82, both categorized as valid. Therefore, the developed jobsheet is considered feasible to be used as a learning medium for electropneumatic control systems in vocational education